Identifying the Components of the Moral and Social Education Curriculum for Lower Secondary Schools in Hormozgan - Almasi , Mohammad; Abedini, Mahnoosh; Rahmani , Mohamadnoor (Iranian Journal of Educational Sociology, 2025)
Purpose: This study aimed to identify and validate the core components of a moral and social education curriculum model tailored for lower secondary schools in Hormozgan Province, Iran. Methods and Materials: The research employed a qualitative design using the classical grounded theory approach as developed by Glaser and Strauss (1967). Data were collected through semi-structured interviews with 30 experts, including educators, curriculum specialists, and policy advisors in the field of moral and social education. Participants were selected based on academic expertise or practical experience in teaching or policymaking for moral education at the lower secondary level. Data analysis was conducted in three coding phases—open, axial, and selective—to construct a comprehensive conceptual model. Coding was manual and iterative, ensuring conceptual saturation through constant comparative analysis. Findings: The findings revealed seven core dimensions of the curriculum model: causal conditions, background conditions, intervening conditions, strategies, main phenomenon, outcomes, and facilitating factors. Causal factors highlighted the need to improve cognitive, emotional, and skill-based educational goals. Strategies emphasized the integration of values into teaching methods, evaluation systems, and technological tools. Intervening conditions such as teacher readiness, institutional support, and infrastructural adequacy were found to be critical. Outcomes included enhanced student engagement, moral reasoning, psychosocial well-being, and teacher awareness. Facilitating factors—such as administrative backing and favorable social attitudes—were identified as pivotal for successful implementation. Conclusion: The proposed model offers a holistic, culturally responsive, and theoretically grounded framework for designing and implementing moral and social education curricula in lower secondary schools. By addressing developmental, institutional, and cultural variables, the model supports the formation of ethically conscious and socially responsible students, adaptable to Iran’s diverse educational contexts.